Flexible and Biocompatible Physical Unclonable Function Anti‐Counterfeiting Label - Hu, Yan‐Wei; Zhang, Tai‐Ping; Wang, Chun‐Feng; Liu, Kai‐Kai; Sun, Yuan; Li, Lei; Lv, Chao‐Fan; Liang, Ya‐Chuan; Jiao, Fu‐Hang; Zhao, Wen‐Bo; Dong, Lin; Shan, Chong‐Xin (Advanced functional materials, 2021)
Optical physical unclonable functions (PUFs) have been proven to be one of the most effective anti‐counterfeiting strategies. However, optical PUFs endowed with flexibility and biocompatibility have not been developed, limiting their application scenarios. Herein, biocompatible and flexible optical PUF labels are developed by randomly embedding microdiamonds in silk fibroin films. The PUF labels can be conformally attached onto the surface of complex shaped objects, providing the desired protection against fake and interior products. In this system, silk fibroin films serve as a flexible and biocompatible substrate, while the Raman signal of the microdiamonds serves as response of the excitation. The extremely high stability and random distribution of the microdiamonds ensure the performance of PUFs, and the maximum encoding capability of 210000 is finally realized. The cytotoxicity analysis results also verify the biosafety of the PUF system. In addition, the as‐prepared PUF labels are attached onto the surface of polyethylene material, and human skin, and even have been implanted under chicken skin tissue, promising their practical applications. Flexible and biocompatible physical unclonable function labels are designed and demonstrated by using microdiamonds as the response of the excitation and silk fibroin films as a flexible and biocompatible substrate, which have been applied for protection against fake objects with complex shapes.